Customer Requirements Mapping Method Based on Association Rule Mining for Mass Customization - 夏世升 王丽亚 (Shanghai jiao tong da xue xue bao, 2008)
Customer requirements analysis is the key step for product variety design of mass customization（MC）. Quality function deployment （QFD） is a widely used management technique for understanding the voice of the customer （VOC）, however, QFD depends heavily on human subject judgment during extracting customer requirements and determination of the importance weights of customer requirements. QFD process and related problems are so complicated that it is not easily used. In this paper, based on a general data structure of product family, generic bill of material （GBOM）, association rules analysis was introduced to construct the classification mechanism between customer requirements and product architecture. The new method can map customer requirements to the items of product family architecture respectively, accomplish the mapping process from customer domain to physical domain directly, and decrease mutual process between customer and designer, improve the product design quality, and thus furthest satisfy customer needs. Finally, an example of customer requirements mapping of the elevator cabin was used to illustrate the proposed method.